The political theorist, Fujita Shōzō: between his sense of hope (kibō) and his sense of despair (zetsubō) - Sakurai, Takamichi (Japanese journal of political science, 2018)
In this article, I describe an important aspect of the intellectual tradition of Japanese political theory while focusing on the Japanese scholar Fujita Shōzō’s political and scholarly activities. Not surprisingly, he has been chiefly considered a thinker or a historian of ideas, due to his being a pupil of Japan's brightest political scientist, Maruyama Masao. It must be stressed, however, that his scholarly works do not confine his academic scope to their ingredients; they are composed of theoretical requisites for the disciplinary activity of political theory, as can be seen particularly in his early contributions. He requires his theory to constitute integral aspects of practice, experience and perspective on the basis of his political concerns and practices in terms of detachment realism. From this perspective, I explore how Fujita changed his primary purpose from criticising Japan's ‘Tennō system’ (Tennōsei) to criticising its ‘high-speed growth’ (kōdo seichō) by highlighting the psychological transformation of his self-critical and self-reflective political thinking and acting according to his optimistic state of ‘hope’ (kibō) and his pessimistic state of ‘despair’ (zetsubō), especially in terms of his early work.
Gesehen am 14.05.2019